Description of Cryptaphelenchus iranicus n. sp. (Nematoda: Ektaphelenchinae) recovered from bark samples of Pinus nigra from Iran - Esmaeili, Mehrab; Heydari, Ramin; Taheri, Zahra Majd; Fang, Yiwu; Li, Hongmei (Zootaxa, 2016)
Cryptaphelenchus iranicus n. sp., recovered from bark and wood samples of a weakened Pinus nigra in Kermanshah Province, western Iran, is described. The new species has females with body length of 250–330 µm and males 230–275 µm long, lip region set-off from body contour, 7–8 μm long stylet with small basal swellings, excretory pore located at 1.5–2.0 body diam. posterior to median bulb, post-vulval uterine sac short, 7–10 µm long and conical female posterior body end (tail) ending to a pointed tip. Males of the new species have seven (1+2+2+2) caudal papillae and a short mucro at tail tip. Based on morphological characters, the new species is close to C. cirrus, C. latus and C. leptocaudus. Phylogenetic analyses using the D2/D3 fragment of 28S rDNA show the new species forming a clade with other Cryptaphelenchus species with maximal (1.00) Bayesian posterior probability (BPP) in Bayesian inference and 100% bootstrap value (BS) in the maximum likelihood method. The Cryptaphelenchus clade forms a monophyletic group with members of subfamily Ektaphelenchinae.